2022
DOI: 10.3390/cancers14225708
|View full text |Cite
|
Sign up to set email alerts
|

The Somatic Mutation Landscape of UDP-Glycosyltransferase (UGT) Genes in Human Cancers

Abstract: The human UDP-glycosyltransferase (UGTs) superfamily has a critical role in the metabolism of anticancer drugs and numerous pro/anti-cancer molecules (e.g., steroids, lipids, fatty acids, bile acids and carcinogens). Recent studies have shown wide and abundant expression of UGT genes in human cancers. However, the extent to which UGT genes acquire somatic mutations within tumors remains to be systematically investigated. In the present study, our comprehensive analysis of the somatic mutation profiles of 10,06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…For example, various UGTs are involved in the glucuronidation of androgens, estrogens, and lipids, molecules with established roles in tumor growth. Further, numerous groups have shown associations between UGT expression levels and cancer prognoses, suggesting the potential to use UGT profiles as predictive and/or prognostic biomarkers (Desai et al, 2003;Dalhoff et al, 2005;Allain et al, 2020a;Hu et al, 2022). Multiple studies have suggested a role for UGT2B17 in affecting the outcome of chronic lymphocytic leukemia treatments, either due to its role in regulating endogenous steroids or through a nonenzymatic mechanism (Gruber et al, 2013;Bhoi et al, 2016;Allain et al, 2019;Allain et al, 2020b).…”
Section: Udp-glucuronosyltransferasesmentioning
confidence: 99%
“…For example, various UGTs are involved in the glucuronidation of androgens, estrogens, and lipids, molecules with established roles in tumor growth. Further, numerous groups have shown associations between UGT expression levels and cancer prognoses, suggesting the potential to use UGT profiles as predictive and/or prognostic biomarkers (Desai et al, 2003;Dalhoff et al, 2005;Allain et al, 2020a;Hu et al, 2022). Multiple studies have suggested a role for UGT2B17 in affecting the outcome of chronic lymphocytic leukemia treatments, either due to its role in regulating endogenous steroids or through a nonenzymatic mechanism (Gruber et al, 2013;Bhoi et al, 2016;Allain et al, 2019;Allain et al, 2020b).…”
Section: Udp-glucuronosyltransferasesmentioning
confidence: 99%
“…41−43 Posttranscriptional regulation will be performed when the miRNAs combine with 3′UTRs regulating the UGT gene expression. 44 For example, the expression of UGT2B was regulated by miR-216b-5p related to liver cancer, 45 and the expression of UGT2A1 was mediated by miR-196b-5p or miR-196a-5p related to the detoxification of some hydrocarbons; 46 the expression of UGT1A1 was mediated by miR-486−3p or miR-214−5p related to the development or progression of liver fibrosis/cirrhosis. 47 Though UGTs play a crucial role in insecticide metabolism in insects, the molecular mechanism affected by insecticides remains unclear in S. miscanthi.…”
Section: Introductionmentioning
confidence: 99%
“…UGT expression could be mediated at both transcriptional and post-transcriptional levels where microRNAs (miRNAs) can act on post-transcriptional regulation by combining with 5′UTRs and 3′UTRs or coding sequences (CDs). Post-transcriptional regulation will be performed when the miRNAs combine with 3′UTRs regulating the UGT gene expression . For example, the expression of UGT2B was regulated by miR-216b-5p related to liver cancer, and the expression of UGT2A1 was mediated by miR-196b-5p or miR-196a-5p related to the detoxification of some hydrocarbons; the expression of UGT1A1 was mediated by miR-486–3p or miR-214–5p related to the development or progression of liver fibrosis/cirrhosis …”
Section: Introductionmentioning
confidence: 99%